The Micro Foundations of Policy Diffusion Toward Complex Global Governance: An Analysis of the Transnational Carbon Emission Trading Network. (March 2014) - Paterson, Matthew; Hoffmann, Matthew; Betsill, Michele; Bernstein, Steven
Greenhouse gas emissions trading (ET) systems have become the centerpiece of climate change policy at multiple scales, unexpectedly largely outside of the UN climate governance process. The diffusion of ET is best described as a case of polycentric diffusion, where ET systems diffused to multiple loci of governance, but where they all serve similar goals under a broad policy framework guided loosely by the UN-based climate regime. Using network analysis combined with qualitative data, we explain how this polycentric pattern of policy development emerged, who carried and spread it and how, and how the idea has spread into a polycentric governance system. We contribute to the policy diffusion literature in a novel way to explain diffusion toward polycentric governance, show the limits of the existing literature to explain the diffusion of ET, and show the utility of network analysis in understanding the process and mechanism of polycentric diffusion.